2021
DOI: 10.1101/2021.05.10.443411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

E3 ubiquitin ligase RNF213 employs a non-canonical zinc finger active site and is allosterically regulated by ATP

Abstract: RNF213 is a giant E3 ubiquitin ligase and a major susceptibility factor of Moyamoya disease, a cerebrovascular disorder that can result in stroke or death. In the cell, RNF213 is involved in lipid droplet formation, lipotoxicity, hypoxia, and NF-κB signaling, but its exact function in these processes is unclear. Structural characterization has revealed the presence of a dynein-like ATPase module and an unprecedented but poorly understood E3 module. Here, we demonstrate that RNF213 E3 activity is dependent on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…The authors suggest that decreased RNF213 E3 ligase activity is central to MMD pathogenesis and they even hypothesize that the extent of impairment might correlate with the level of penetrance of a certain MMD polymorphism. Interestingly, the RNF213 E3 module contains two E3 catalytic domains, a classic RING domain, [54,61] and a noncanonical RZ finger recently described by Otten et al [58] (Figure 2). While the RZ finger is responsible for the ubiquitylation of bacterial lipopolysaccharide (LPS) [58], other (non-)proteinaceous substrates might exist, and further research is needed to elucidate the function and full substrate repertoire of both catalytic domains.…”
Section: Rnf213 Is a Giant Multifunctional Proteinmentioning
confidence: 94%
“…The authors suggest that decreased RNF213 E3 ligase activity is central to MMD pathogenesis and they even hypothesize that the extent of impairment might correlate with the level of penetrance of a certain MMD polymorphism. Interestingly, the RNF213 E3 module contains two E3 catalytic domains, a classic RING domain, [54,61] and a noncanonical RZ finger recently described by Otten et al [58] (Figure 2). While the RZ finger is responsible for the ubiquitylation of bacterial lipopolysaccharide (LPS) [58], other (non-)proteinaceous substrates might exist, and further research is needed to elucidate the function and full substrate repertoire of both catalytic domains.…”
Section: Rnf213 Is a Giant Multifunctional Proteinmentioning
confidence: 94%
“…However, Otten and colleagues mapped a molecular motif within the E3 module, named RZ‐finger, that is typical for zinc‐binding domains, and showed that it is required for LPS ubiquitylation. Recent biochemical studies pinpointed an active site cysteine within the RZ finger that accepts Ub from the E2 enzyme UBCH7, suggesting that RNF213 represents an undescribed type of transthiolation E3 enzyme (preprint: Ahel et al , 2021). RNF213 knockout mouse embryonic fibroblasts (MEFs) or cells expressing RNF213 mutations corresponding to the RZ‐finger are severely defective in Ub coat formation around cytosolic Salmonella and also failed to recruit LUBAC and lacked LUBAC‐mediated M1 Ub chain synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…RNF213 is a giant 600 kDa protein with a unique structure that combines a dynein-like ATPase core with a RINGtype E3 ligase domain (Figure 1; Ahel et al, 2020). Interestingly, the RING domain is not required for auto-ubiquitination or for LPS ubiquitination (Otten et al, 2021;Ahel et al, 2020;Ahel et al, 2021). Instead, an adjacent zinc-binding ''RZ'' domain uses a cysteine-dependent mechanism to conjugate ubiquitin, akin to the HECT, RBR, and RCR families of E3 ligases (Otten et al, 2021;Ahel et al, 2021).…”
mentioning
confidence: 99%
“…Interestingly, the RING domain is not required for auto-ubiquitination or for LPS ubiquitination (Otten et al, 2021;Ahel et al, 2020;Ahel et al, 2021). Instead, an adjacent zinc-binding ''RZ'' domain uses a cysteine-dependent mechanism to conjugate ubiquitin, akin to the HECT, RBR, and RCR families of E3 ligases (Otten et al, 2021;Ahel et al, 2021). Recent structural work by the Clausen and Virdee laboratories has described the mechanism of ubiquitin conjugation employed by RNF213 and identified a role for the ATPase core in regulating ligase activity through sensing ATP levels (Ahel et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation